Wayground Game Media for Understanding the Material in Science and Social Learning for Student in Elementery School - Afina Dwi Astuti Fina; Heny Kusmawati (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2026)
The low level of understanding among 4th-grade students at MI Miftahul Huda Sukobubuk regarding the topics of cultural diversity and local wisdom in IPAS lessons served as the background for this study, given that conventional teaching methods were deemed insufficient in stimulating students’ interest and active engagement. This study aims to describe strategies for utilizing the Wayground game as a teaching medium and to analyze its effectiveness in improving students’ understanding of these topics. The method used is a descriptive qualitative approach involving direct field research. Data were collected through non-participant observation, in-depth interviews with the madrasah principal, 4th-grade teachers of classes A and B, and students, as well as documentation of learning activities. The data were then analyzed using the Miles and Huberman interactive model, which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that the use of Wayground was implemented in three stages: preparation of materials on the platform; implementation utilizing classroom TVs, computer labs, and the school’s Wi-Fi, and evaluation through an automatic assessment feature that displays students’ scores in real time. This medium proved effective in increasing students’ enthusiasm, motivation, and understanding of the subject matter on cultural diversity and local wisdom. However, the effective use of Wayground is still hampered by technical challenges, namely its reliance on a stable internet connection, which, if not maintained, can disrupt the learning process.